Sedimentary mercury enrichments as a marker for submarine Large Igneous Province volcanism? Evidence from the Mid-Cenomanian Event and Oceanic Anoxic Event 2 (Late Cretaceous) - Scaife, J; Ruhl, M; Dickson, A; Mather, T; Jenkyns, H; Percival, L; Hesselbo, P; Cartwright, J; Eldrett, J; Bergman, S; Minisini, D (American Geophysical Union, 2017)
Oceanic Anoxic Event 2 (OAE 2), during the Cenomanian‐Turonian transition (∼94 Ma), was the largest perturbation of the global carbon cycle in the mid‐Cretaceous and can be recognized by a positive carbon‐isotope excursion in sedimentary strata. Although OAE 2 has been linked to large‐scale volcanism, several large igneous provinces (LIPs) were active at this time (e.g., Caribbean, High Arctic, Madagascan, Ontong‐Java) and little clear evidence links OAE 2 to a specific LIP. The Mid‐Cenomanian Event (MCE, ∼96 Ma), identified by a small, 1‰ positive carbon‐isotope excursion, is often referred to as a prelude to OAE 2. However, no underlying cause has yet been demonstrated and its relationship to OAE 2 is poorly constrained. Here we report sedimentary mercury (Hg) concentration data from four sites, three from the southern margin of the Western Interior Seaway and one from Demerara Rise, in the equatorial proto‐North Atlantic Ocean. We find that, in both areas, increases in mercury concentrations and Hg/TOC ratios coincide with the MCE and the OAE 2. However, the increases found in these sites are of a lower magnitude than those found in records of many other Mesozoic events, possibly characteristic of a marine rather than atmospheric dispersal of mercury for both events. Combined, the new mercury data presented here are consistent with an initial magmatic pulse at the time of the MCE, with a second, greater pulse at the onset of OAE 2, possibly related to the emplacement of LIPs in the Pacific Ocean and/or the High Arctic.